2014
DOI: 10.1038/srep04285
|View full text |Cite
|
Sign up to set email alerts
|

Orientation tuning in human colour vision at detection threshold

Abstract: We measure the orientation tuning of red-green colour and luminance vision at low (0.375 c/deg) and mid (1.5 c/deg) spatial frequencies using the low-contrast psychophysical method of subthreshold summation. Orientation bandwidths of the underlying neural detectors are found using a model involving Minkowski summation of the rectified outputs of a bank of oriented filters. At 1.5 c/deg, we find orientation-tuned detectors with similar bandwidths for chromatic and achromatic contrast. At 0.375 c/deg, orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 63 publications
1
25
1
Order By: Relevance
“…Subsequent psychophysical studies, however, suggested that bandpass spatial filtering with broadly similar bandwidths for color and achromatic contrast underlies the overall low-pass shape of the CSF (Bradley, Switkes, & De Valois, 1988;Humanski & Wilson, 1992;Losada & Mullen, 1994Mullen & Losada, 1999). Furthermore, psychophysical studies have demonstrated orientation tuned responses in color vision (Beaudot & Mullen, 2005;Bradley et al, 1988;Humanski & Wilson, 1993;Reisbeck & Gegenfurtner, 1998;Vimal, 1997;Webster, Switkes, & Valois, 1990;Wuerger & Morgan, 1999), although this may be lost at very low spatial frequencies (Gheiratmand, Meese, & Mullen, 2013;Gheiratmand & Mullen, 2014). Thus, the presence of both spatial frequency and orientation tuning neural responses, the prerequisites for edge detection, suggest that there may be a system for chromatic edge detection.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent psychophysical studies, however, suggested that bandpass spatial filtering with broadly similar bandwidths for color and achromatic contrast underlies the overall low-pass shape of the CSF (Bradley, Switkes, & De Valois, 1988;Humanski & Wilson, 1992;Losada & Mullen, 1994Mullen & Losada, 1999). Furthermore, psychophysical studies have demonstrated orientation tuned responses in color vision (Beaudot & Mullen, 2005;Bradley et al, 1988;Humanski & Wilson, 1993;Reisbeck & Gegenfurtner, 1998;Vimal, 1997;Webster, Switkes, & Valois, 1990;Wuerger & Morgan, 1999), although this may be lost at very low spatial frequencies (Gheiratmand, Meese, & Mullen, 2013;Gheiratmand & Mullen, 2014). Thus, the presence of both spatial frequency and orientation tuning neural responses, the prerequisites for edge detection, suggest that there may be a system for chromatic edge detection.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (2008) did report that the V1 neurons most biased towards L/ M gratings and away from luminance gratings did prefer lower spatial frequencies, and some were poorly tuned for orientation. This has also been reported psychophysically (Gheiratmand & Mullen, 2014). While most V1 neurons might respond differentially to color stimuli to some exten/t, it is still not clear whether all these neurons contribute to color perception, or whether this is the role of some (yet to be characterized) subset of neurons (Schmidt et al, 2014(Schmidt et al, , 2016.…”
Section: Modeling the Color Planesmentioning
confidence: 67%
“…In sum, relative to component gratings, color plaids have lower perceived contrast summation than achromatic plaids and this chromatic summation difference is greater at the medium-spatial frequency and smaller at the low-spatial frequency. These results may be reflective of two separate processes: greater cross-orientation suppression in color vision (Kim et al, 2013; Medina & Mullen, 2009) and increased cross-orientation summation for low compared with medium-spatial frequency color stimuli (Gheiratmand et al, 2013, 2016; Gheiratmand & Mullen, 2014). …”
Section: Resultsmentioning
confidence: 92%
“…Moreover, this effect is greater for mid-spatial frequency stimuli; for this spatial frequency, chromatic plaids have the lowest perceived contrast summation while achromatic plaids have the highest. Recent research on cross-orientation effects in color vision has identified two different and specific mechanisms: subthreshold summation, which acts to increase contrast sensitivity to cross-oriented stimuli (Gheiratmand et al, 2013, 2016; Gheiratmand & Mullen, 2014), and cross-orientation suppression, which decreases contrast sensitivity when one cross-oriented component is at a suprathreshold contrast (Kim et al, 2013; Medina & Mullen, 2009). We next discuss how the presence of these mechanisms in suprathreshold plaid contrast perception is supported by our data.…”
Section: Discussionmentioning
confidence: 99%